2008
DOI: 10.1007/s00418-008-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes in the mature chorioallantoic membrane capillary plexus contain desmin and α-smooth muscle actin: relevance for non-sprouting angiogenesis

Abstract: The chicken chorioallantoic membrane (CAM) is a frequently used tissue for studying vascular growth and remodeling, notably non-sprouting angiogenesis by formation of transluminal pillars. Vascular pericytes have received increasing attention in the field of angiogenesis research and appear important for pillar growth. Our earlier observation that desmin (DES), but not alpha-smooth muscle actin (alphaSMA) was expressed in pericytes of the mature CAM capillary plexus after E12 was confirmed by others. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…It was previously demonstrated that SMA is present in the CAM capillary plexus, and its expression is intimately related to its endothelial layer at least after day 12 of incubation (16). Although the anti-SMA antibody was human specific, it was clearly positive in a population of cMSC and the chick pericytes.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It was previously demonstrated that SMA is present in the CAM capillary plexus, and its expression is intimately related to its endothelial layer at least after day 12 of incubation (16). Although the anti-SMA antibody was human specific, it was clearly positive in a population of cMSC and the chick pericytes.…”
Section: Discussionmentioning
confidence: 92%
“…What impresses in the SMA is its high expression in the angiogenic and vasculogenic areas, as it proves the close contact of the pericyte-like cells with the new capillaries, but also with CLS, even if they do not present a lumen yet. It is clear that SMA is needed for the stability of the pseudopode like projections present in the pericytes (16), offering a consecutive stability to the vessel wall, but the question is why is this SMA expressed so early in the cMSC? It was hypothesized that pericytes are recruited towards the capillary plexus early in CAM development (before day 10 of incubation) (16) and VEGF seems to stimulate this process (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intusseptive angiogenesis, nonsprouting angiogenesis by means of transluminal pillars and folds, has been extensively studied in the chicken chorionallantoic membrane (CAM; Kurz et al 2003), and pericytes have been shown to be important for this process. Kurz et al (2008a), using triple labelling with Xuorochrome-conjugated markers Sambucus nigra agglutinin, desmin (DES) or smooth muscle actin ( SMA), and DNA staining and confocal analysis, documented the presence of a delicate Wlamentous SMA-immunolabeling and a coarser, axially oriented DES-immunolabelling pattern in periendothelial cells of the mature CAM capillary plexus. Additionally, they developed a new automatic classiWcation method for DNA staining patterns to compare nuclei of DES or SMA-immunoreactive cells.…”
Section: Endothelium Pericytes and Angiogenesismentioning
confidence: 99%